2018
DOI: 10.1016/j.physletb.2018.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Soft pomerons and the forward LHC data

Abstract: Recent data from LHC13 by the TOTEM Collaboration on σ tot and ρ have indicated disagreement with all the Pomeron model predictions by the COMPETE Collaboration (2002). On the other hand, as recently demonstrated by Martynov and Nicolescu (MN), the new σ tot datum and the unexpected decrease in the ρ value are well described by the maximal Odderon dominance at the highest energies. Here, we discuss the applicability of Pomeron dominance through fits to the most complete set of forward data from pp andpp scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The recent TOTEM results [4,5] generated a burst of high level and intense theoretical debate about the correct interpretation of these data, see Refs. [15][16][17][18][19][20][21][22][23][24][25][26][27]. All possible extreme views were present among these first interpretative papers, including claims for a maximal Odderon effect [23] and claims of lack of any significant Odderon effects, Refs.…”
Section: Odderonmentioning
confidence: 99%
“…The recent TOTEM results [4,5] generated a burst of high level and intense theoretical debate about the correct interpretation of these data, see Refs. [15][16][17][18][19][20][21][22][23][24][25][26][27]. All possible extreme views were present among these first interpretative papers, including claims for a maximal Odderon effect [23] and claims of lack of any significant Odderon effects, Refs.…”
Section: Odderonmentioning
confidence: 99%
“…The main motivation for this is our need to describe the energy behaviour of the ratio ρ = Re/Im of the scattering amplitude, to which the secondary reggeons make a significant contribution. The new TOTEM data [12] shows that the value of ρ = 0.1 ± 0.01(0.09 ± 0.01) is lower than expected, and this ignited the hot discussion about the possible contribution of the odderon [13][14][15][16][17][18][19][20]. The odderon contribution to the negative signature appears naturally in perturbative QCD, with an intercept which is equal to zero [21,22].…”
mentioning
confidence: 99%
“…In the second analysis, we have considered one Pomeron model with 6 free parameters and have evaluated the uncertainty regions with confidence level (CL) of 90 %. We have concluded that the model seems not to be excluded by the bulk of experimental data presently available [27].…”
Section: Introductionmentioning
confidence: 80%